Core Framing terhadap Penggunaan Tafsir Ibnu Katsir di Media Online - Muhamad Yoga Firdaus (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
This research was born because of the rise of societal hegemony in the digital era towards Islamic presentations, especially in the treasures of Al-Qur'an interpretation using books written by a mufasir who carries a certain construction. This study aims to discuss the core framing of the use of Tafsir Ibnu Katsir in online media. This research method is qualitative through literature and field studies using media framing theory. The results of this study are to show that core framing is attached to the accumulation of presentation analysis through opening, critical thinking, brainstorming, argumentation, symbols, data and facts, moral claims, closing as well as the core idea of ​​using the source Tafsir Ibnu Katsir on the Islami.co and Bincangsyariah.com websites , namely a peaceful and comprehensive Islamic discourse through the insertion of peaceful narratives and explanations of Al-Qur'an verses both textually and contextually in the presentation. This research is present as a neat effort so that an authoritative and trustworthy study of the Qur'an is not limited to the dimensions of space and time. Studies of the Qur'an can also be present in an accommodative manner and are easily accessible to all groups.